Respostas
respondido por:
0
2x-3y=-9
x+4y=12. (-2)
2x-3y=-9
-2x-8y= -24
Corta os 2 pois são simétricos
-11y=-33 (-1)
Multiplica por menos 1 pois o y está negativo
11y=33
y=33/11
y=3
x+4y=12
x+4.3=12
x+12 =12
x= 12-12
x=0
x+4y=12. (-2)
2x-3y=-9
-2x-8y= -24
Corta os 2 pois são simétricos
-11y=-33 (-1)
Multiplica por menos 1 pois o y está negativo
11y=33
y=33/11
y=3
x+4y=12
x+4.3=12
x+12 =12
x= 12-12
x=0
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás